PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Zahroh, Rafiqa Choridatuz; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this study is to identify and analyze the effects of work motivation, workplace environment, and job satisfaction on the turnover intention of employees of Bank Rakyat Indonesia in the branch office of Malang Kawi. This quantitative explanatory research explains the relationship of a variable with other variables through hypothesis testing. Using non-probability sampling method and saturated sampling technique, all seventy employees of Bank Rakyat Indonesia in the branch office of Malang Kawi were selected as the respondents. The research data was analyzed using multiple linear regression in SPSS version 25. This study finds that work motivation, workplace environment, and job satisfaction partially have negative and significant effects on turnover intention. This means that work motivation, workplace environment, and job satisfaction are factors contributing to the emergence of employees’ turnover intention.